The Main Purpose of Islamic Sharia in Environmental Conservation - La Ode Angga (Universitas Kebangsaan Republik Indonesia [UKRI], 2020)
In the perspective of Islamic law (read: Jurisprudence), the preservation of the earth and human responsibility for nature and the environment, actually has long been discussed. Efforts to develop the fiqh of the earth and formulate it into more systematic and practical frameworks need to be worked on immediately. Classic fiqh content that discusses environmental themes separately and abstractly needs to be given ecological weight. For example, discussions in classical Jurisprudence books, such as the chapter taharah (purification), shaid (hunting), ihya 'al-mawat (utilizing dead land), al-'at`imah (law on food), sharibah (law on drinks), etc. From here, fiqh of the earth can be an entry point towards strengthening the role's capacity. Not only to protect the earth, jurisprudence of the earth also has a role to sustain the global movement on the issue of sustainable nature conservation. In this context, fiqh of the earth can be the vanguard for strengthening the capacity of Islamic law in modern life.In this case, there are several values that must be guided as a practical basis in formulating and developing fiqh of the earth, including: a. The creation of the universe including the environment of the human cosmos (land, water and air) has determined qadar (size or stipulation) which must always be maintained and preserved. So whoever destroys it means that it has corrupted the qadar of Allah. This is as confirmed in the Surah al-Hijr verse: 19-20: